ДИАЛОГ В КУЛЬТУРЕ: ВОЗМОЖНОСТИ И ОГРАНИЧЕНИЯ - ТКАЧЕВА, Е. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
В данной статье рассматриваются проблемы возможностей и ограничений диалогакультур в современном обществе. Автор анализирует ситуации взаимодействия культур иосуществляет попытку рассмотреть возможности диалога культур в условияхглобализации, а также уточнить принципы организации диалога между современнымицивилизациями под углом зрения их социокультурных систем.О.В. Ткачова ДІАЛОГ В КУЛЬТУРІ: МОЖЛИВОСТІ ТА ОБМЕЖЕННЯ У данійстатті розглядаються проблеми можливостей та обмежень діалогу культур у сучасномусуспільстві. Авторка аналізує ситуації взаємодії культур та здійснює спробу розглянутиможливості діалогу культур в умовах глобалізації, а також уточнити принципи організаціїдіалогу___________________© Ткачева Е.В. , 2011Ключові слова: діалог, мультикультуралізм, толерантність, культурна ідентичність,глобалізація.E. Tkacheva DIALOGUE IN THE CULTURE: POSSIBILITIES AND LIMITS This articlediscusses the problem of the opportunities and constraints of cultural dialogue in modern society.The author analyzes the situation of interaction between cultures and attempts to consider thepossibilities of intercultural dialogue in the context of globalization, as well as to clarify theprinciples of dialogue between contemporary civilizations from the perspective of their socioculturalsystems.Keywords: dialogue, multiсulturalism, tolerance, cultural identity, globalization